Selective electron beam melting - A novel generative manufacturing technique for cellular titanium - Heinl, Peter; Körner, Carolin; Singer, Robert (5th International Conference on Porous Metals and Metallic Foams, MetFoam 2007, 2008)
Cellular titanium seems to be a promising material for medical implant applications due to an elastic modulus comparable with human bone and an interconnected porosity which facilitates bone ingrowth. The production of cellular titanium based on standard techniques for cellular materials is associated with various difficulties, e.g. the high reactivity of liquid titanium, which generally leads to strong degradation of the mechanical properties of the matrix material. For the production of titanium components with a cellular structure we use the Selective Electron Beam Melting (SEBM) technology, which belongs to the generative manufacturing techniques. Degradation of the matrix material is completely prevented since production is in high vacuum. In this paper, the fundamental principles of the SEBM process and two different approaches to generate cellular titanium structures are described. Furthermore generated structures are characterised by micro computer tomography and the mechanical properties of different cellular titanium structures are presented.